The role of ghost rocks (phantomisation) in the formation of the Sterkfontein cave and the Gauteng karsts (South Africa) - (:unkn) unknown (My University, 2022)
The Neoarchean dolomites of the Gauteng province, in South Africa, contain numerous cavities including the Sterkfontein Cave, famous for its Plio‐Pleistocene fossil deposits. This network, measuring several kilometers in length, represents a true three‐dimensional maze cave. This characteristic has been described as a manifestation of either hyperphreatic or hypogenic karstification processes. Our work in this cave over the last fifteen years has led us to discover large quantities of weathered dolomite remaining in situ (ghost rock), emulating the structure of the original rock. We suggest that this network was formed through phantomisation associated with a long period of alteration correlated with the development of the African Surface. Through the down cutting of the hydrographic network, the soft sandy alterite was easily evacuated, exposing the residual passages and chambers of the cave system, but leaving morphologies usually attributed to more classic karstification processes. In the contemporary Sterkfontein Cave, we can still witness the removal of the ghost rock and its association with the fluctuations of the karstic base level. The observations made here can be extrapolated to all the Gauteng karst, where occurrences of comparable alterites are widely represented and pose recurring geotechnical challenges.
Keywords: African Research